2018
DOI: 10.1016/j.amjcard.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Extensive Myocardial Fibrosis in Nonhigh Risk Patients With Hypertrophic Cardiomyopathy

Abstract: In nonhigh risk patients with hypertrophic cardiomyopathy (HC), the presence of extensive late gadolinium enhancement (LGE) at cardiovascular magnetic resonance (CMR) imaging has been proposed as a risk modifier in the decision process for implantable cardioverter defibrillator implantation. With a pretest risk of about 10%, a strategy that alters the likelihood of LGE could markedly affect efficacious CMR imaging. Our aim was to study the potential of clinical variables and biomarkers to predict LGE. In 98 HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
(28 reference statements)
2
15
1
Order By: Relevance
“…Our biomarker panel also included: N-terminal-pro-B-type-Natriuretic Peptide, Galectin-3, soluble Tumorigenicity Suppressor2, Growth Differentation Factor-15 and C-terminal Propeptide of Type I Collagen (CICP (Appendix for detailed description of the assays). 5 Variability and performance in healthy controls and patients with heart failure have been published. 12 CMR imaging with cine, LGE and T2-weighted sequences was performed on 1.5T CMR systems (Philips Achieva (Philips Healthcare, Best, The Netherlands) or (Siemens Avanto (Siemens Health Care, Erlangen, Germany)) according to local imaging protocols, as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our biomarker panel also included: N-terminal-pro-B-type-Natriuretic Peptide, Galectin-3, soluble Tumorigenicity Suppressor2, Growth Differentation Factor-15 and C-terminal Propeptide of Type I Collagen (CICP (Appendix for detailed description of the assays). 5 Variability and performance in healthy controls and patients with heart failure have been published. 12 CMR imaging with cine, LGE and T2-weighted sequences was performed on 1.5T CMR systems (Philips Achieva (Philips Healthcare, Best, The Netherlands) or (Siemens Avanto (Siemens Health Care, Erlangen, Germany)) according to local imaging protocols, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 In that regard, it is surprising that the role of cardiac troponin (cTn) in HC patients has not been extensively studied. [4][5][6][7] Elevated cTn is a common finding and associated with adverse disease characteristics, such as wall thickness and late gadolinium enhancement (LGE). [4][5][6][7][8] In 2013, the first report was published that demonstrated an association between elevated cTnT, assessed with a high-sensitivity assay (hs-cTnT) and adverse long-term outcome in HC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This strongly suggests that in HCM, Gal-3 is predominantly related to HF severity, which is corroborated by the observation that no association between Gal-3 levels and LV hypertrophy exists in HCM patients with predominantly mild HF symptoms [73]. In addition, Gal-3 plasma levels did not correlate with LGE-detected fibrosis in HCM patients [73,77,111]. For GDF15, plasma levels were also associated with disease severity in HCM patients [112].…”
Section: Non-cardiac-specific Plasma Biomarkers In Hcm Dcm and Acmmentioning
confidence: 65%
“…Interestingly, it was shown that exercise increased BNP plasma levels particularly in HCM patients with silent ischemia [75]. Importantly, BNP and cTn levels were also associated with fibrosis in HCM patients and cTn levels were predictive for the detection of extensive myocardial fibrosis in non-high risk patients with HCM [76,77]. Troponin measurements could therefore be used as a pretest to select patients for CMR imaging with LGE or T1 mapping to establish cardiac fibrosis.…”
Section: Nps and Troponins In Hcm Dcm And Acmmentioning
confidence: 99%